Soybean Cost-Return Budget (W-SB-F Rotation) in Western Kansas - O'Brien, Daniel M.; Dumler, Troy J.; Thompson, Curtis R. (My University, 1999)
This publication contains information for a projected budged reflecting expected income and cost based on soybean production practices in western Kansas.
MF2366_1999_10
Keywords: MF2366; Economics; Crops; MF